2023
DOI: 10.1590/1677-5449.202000531
|View full text |Cite
|
Sign up to set email alerts
|

Comparação das alterações angiográficas entre pacientes diabéticos e não diabéticos com doença arterial periférica

Abstract: Resumo Contexto Os diabéticos possuem risco de 5 a 15 vezes maior para o desenvolvimento de doença arterial periférica (DAP), e poucos estudos compararam fatores de risco e a distribuição e gravidade de alterações arteriais angiográficas entre diabéticos e não diabéticos. Objetivos Comparar alterações angiográficas entre pacientes diabéticos e não diabéticos com DAP avançada, correlacionando-as com demais fatores de risco. Métodos Trata-se de um estudo transversal retrospectivo de pacientes consecutivos sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(137 reference statements)
0
0
0
1
Order By: Relevance
“…In Brazil, a study of angiographic findings in PAD found that diabetic patients exhibited a predominance of lesions classified as TASC A and B in the femoropopliteal zone, whereas non-diabetics had a predominance of TASC C and D classifications, indicating more advanced injuries. 23 Histologically, a study showed that the pattern of atherosclerosis in the arteries of the leg is similar in diabetics and non-diabetics. 24 Other authors studied type 2 DM patients with symptomatic PAD, finding an influence from glycated hemoglobin (HbA1c) on the pattern of the anatomic distribution of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, a study of angiographic findings in PAD found that diabetic patients exhibited a predominance of lesions classified as TASC A and B in the femoropopliteal zone, whereas non-diabetics had a predominance of TASC C and D classifications, indicating more advanced injuries. 23 Histologically, a study showed that the pattern of atherosclerosis in the arteries of the leg is similar in diabetics and non-diabetics. 24 Other authors studied type 2 DM patients with symptomatic PAD, finding an influence from glycated hemoglobin (HbA1c) on the pattern of the anatomic distribution of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…A possível interpretação desses resultados é que os diabéticos, mais frequentemente que os não diabéticos, apresentam comprometimento apenas do território infrapatelar, mantendo a perviedade dos territórios aortoilíaco e femoropoplíteo. No Brasil, um estudo sobre as alterações angiográficas na DAP constatou que doentes diabéticos apresentaram predomínio das lesões nas classificações TASC A e B no território femoropoplíteo, enquanto os não diabéticos tiveram predomínio das classificações TASC C e D, denotando lesões mais avançadas 23 . Histologicamente, uma pesquisa revelou que o padrão de aterosclerose das artérias da perna é semelhante em diabéticos e não diabéticos 24 .…”
Section: Discussionunclassified